Eksistensi Hukum Islam dalam Sistem Waris Adat yang Dipengaruhi Sistem Kekerabatan Melalui Penyelesaian al-Takharujj - Shesa, Laras; Hasim Harahap, Oloan Muda; Elimartati, Elimartati (Institut Agama Islam Negeri Curup, 2021)
The purpose of this study is to find out how much the existence of Islamic law in the indigenous heir system influenced kinship systems through peaceful paths and some used al-takharuj settlement. Using the method of research of library studies sourced from many library references both electronic literature and nonelectronics. Analysis with qualitative and inductive techniques, so it can draw conclusions that corroborate normative values. The results of the study revealed that the resolution of inherited problems in the indigenous heir system remained concerned with the decisiveness of Islamic heirs through the path of settlement of al-takharujj and there were also those based on the principle of Islah. It is also in line with what is embraced in the Compilation of Islamic Law in article 183 on the heirs' agreement with peace in terms of the division of the estate. In its settlement there is one first described about the legally divided division of Islam then shared inheritance customary. Yet some are directly shared directly in customary heirs although it has not been described in an Islamic heir but still uses the principle of ishlah. Thus Islamic law remains recognized its existence in the settlement of customary inheritance although in its implementation it is not carried out thoroughly.